Pre-analytical errors in clinical chemistry laboratory of a tertiary care hospital - Prasad, Priyanka; Kumar, Rakesh; Kumari, Rekha (International Journal of Research in Medical Sciences, 2019)
Background: Pre-analytical errors account for up to 70% of all mistakes made in laboratory diagnostics, most of which arise from problems in patient preparation, sample collection, transportation, and preparation for analysis and storage. Pre-analytical errors influence the total error thus hindering TQM in laboratory, consequently decreasing the accuracy and reliability of the results generated. This study was conducted with the aim to determine nature and frequency of the occurrence of pre-analytical errors. Methods: This prospective analytical study was designed to evaluate the pre-analytical errors observed in a total of 13,892 out-patient and inpatient samples. Samples received for routine clinical chemistry analysis were screened for pre-analytical errors. Samples received for other investigations were excluded. We recorded all nonconformities and errors occurring over a 3-month period and corrective measures were suggested to minimise them. Laboratory personnel were asked to register rejections, and pre-analytical causes for rejection of ward as well as out-patient samples collected in the laboratory. Types of inappropriateness were evaluated as follows: hemolyzed, blood collection in wrong tubes, clotted blood, inappropriate timing of collection, improperly labelled samples, insufficient volume of specimen and lipemic samples. Results: A total of 13,892 samples from the outpatient department and in-house patients were received by our clinical biochemistry laboratory during the period from April 2019 to June 2019. Out of these 404 samples were found unsuitable for further processing. This accounted for 2.9% of all samples collected in the laboratory and pre-analytical errors were responsible for these samples to be rejected over a period of 3 months. Rejections arose as a result of the following reasons: 0.92% were rejected due to hemolysis; 0.58% were blood collected in wrong tubes; 0.55% were clotted blood; 0.26% had inappropriate timing of collection; 0.24% were mislabeled samples; 0.20% had insufficient sample quantity and 0.14% were lipemic samples. Conclusions: Of all the samples received in the lab, the overall percentage of rejection is 2.9%. Substantial number of samples undergo repeated testing because of rejection owing to pre-analytical errors. The efforts should be aimed to reduce the rates of rejected samples can provide to improve the quality of laboratory based health care processes.